(untitled) (Journal of actual problems of jurisprudence, 2019)
This article reviews the essence, types and structure of environmental risks in the subsoil use sphere. It has been defined that a variety risks associated with the environment is covered by the single term which is “environmental risks”. The environmental risk is understood as a beforehand evaluated probability and an extent of hazard that in any man-made intervention into the environment disturbances may arise that can be unfavorable for further functioning and existence of environmental systems both in the man-made effect zone and beyond its limits. It has been demonstrated that works executed in the subsoil use sphere considerably affect the environment. On the basis of researches performed that author provides a comprehensive definition of the “environmental risk” term, formulates its main characteristics and structural elements. Keywords: environmental risks, environment, land, land use, insurance risks.